Interleukin 5 as a therapeutic target in severe asthma - Bajer, Hubert; Pawliczak, Rafał (Alergologia Polska - Polish Journal of Allergology, 2026)
Asthma is a chronic inflammatory disease of the airways, the severe forms of which can lead to severe exacerbations and significant deterioration in quality of life. One of the key mediators of the eosinophilic inflammation characteristic of severe asthma is interleukin 5 (IL-5). IL-5 stimulates the maturation, activation, and migration of eosinophils into the airways, where they cause epithelial damage and exacerbate disease symptoms. Given the important role of IL-5 in the pathogenesis of severe eosinophilic asthma, novel biologic therapies using the monoclonal antibodies mepolizumab, reslizumab, and benralizumab have been developed. Mepolizumab blocks free IL-5, reducing the number of eosinophils and reducing the need for oral corticosteroids. Reslizumab neutralizes IL-5, improving lung function and reducing the frequency of exacerbations. Benralizumab binds to the IL-5 receptor, leading to almost complete elimination of eosinophils. These therapies significantly improve asthma control, reducing symptoms and the risk of exacerbations. However, their use is associated with potential problems, such as allergic reactions, increased risk of infection, and the high cost of therapy, which may limit its availability. Nevertheless, IL-5 blockade represents a breakthrough in the treatment of severe asthma, offering patients an effective alternative to standard corticosteroid therapy.